Governance, Investors Motivations and Foreign Direct Investment Inflow in Selected African Countries: Does John Dunning’s Eclectic Paradigm Matters? - Aberu, Felix (Journal of Legal Studies, 2023)
Over the years, studies have focused on the implications of institutional quality as a key factor of FDI inflows into Africa and how it influences the economic processes of various African countries. However, in the studies on Africa, investors’ motivations as determinants of foreign direct investment inflows into African regions are grossly understudied and yet determined. As a result, there is a need to investigate the impact of FDI inflows on African countries, as well as the implications of home and host country investment phenomena. The study employs ex-post-facto research using panel data obtained from different World Bank publications; world development indicators, and the Transparency Index database from 1997 to 2022. The System Generalized Method of Moments (SGMM) was used to examine the data. The results reveal that governance and investor motivations have a negative impact on each other; the effect of the interacted variables is less than the total of the impacts of governance and investor motivations separately. Therefore, FDI in the selecte3d African countries will decline by 7.5 points for every unit increase in the level of poor governance and investor motivations, and this validates the locational assumption of John Dunning Eclectic Paradigm with the proposition that FDI inflows is a function of the home and host investment phenomena As a result, we recommend that African governments implement Regulatory reform, market reform, complete streets policies, and contingency-based planning that are FDI inflow induced.